Beyond policing: what better way to make the case for a police-free world than to show a world where it's possible - McHarris, Philip V. (Legacy)
"What better way to make the case for a police free world than to show a world where it's possible? For Princeton University's Presidential Postdoctoral Fellow, Philip V. McHarris, body cameras, de-escalation training, procedural justice, diversity among police, and other popular reforms will never stop police violence. And high emphasis on punishment in the United States has left many communities without the resources needed to keep them safe. Beyond Policing aims to provide a better understanding of the origins and functions of policing and the criminal punishment system in the United States. In this research-driven collection of essays, author and sociologist Philip V. McHarris charts the pitfalls of policing in the United States, from slave patrols, to the expansion of mass policing in the mid-1900s, and the epidemic of police violence today. Written in deftly precise, yet widely accessible language, Beyond Policing presents evidence, both data and anecdotal, that tackles the weight and toll of policing on people and communities and patterns that prove that police reform only leads to more policing. And for what seems like America's most oppressive institution, McHarris points to an exit from the current punitive paradigm, outlining strategies for responding to conflict and harm in ways that transform the conditions that gave rise to violence. This requires, he asserts, decriminalization, decarceration, and defunding punitive institutions that have created the current police and carceral state and a committed investment in community-based alternatives-mechanisms that actually provide safety"--